Bullying on the pixel playground: Investigating risk factors of cyberbullying at the intersection of children’s online-offline social lives - Steven J. Seiler; Jordana N. Navarro (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2014)
Although cyberbullying as a serious social problem has received significant attention within the mass media as well as among researchers, experiences of cyberbullying among children in the U.S. are still occurring (Dean, 2012; Salazar, 2010). The purpose of this study was to examine the relationship between social factors (i.e., sociability, social networking site use, Internet use via cell phones), risky online behaviors (i.e., lying about age, sexting, and harassing others), children’s emotional attachment to interactions within SNS, and parental involvement in children’s online social lives on the likelihood of being victims of cyberbullying as well as offline bullying. We found that increased sociability and parental involvement decreased the likelihood of being both cyberbullied and being bullied offline; daily SNS use, Internet use via cell phones, emotional attachment to interactions within SNS, and engaging in risky online behaviors increased the likelihood of being both cyberbullied and bullied offline. The findings suggest (1) cyberbullying is not categorically distinct from offline bullying; (2) future research is necessary to explore the qualitative impact of various risky online behaviors on both online and offline bullying; and (3) research is necessary to further understand the qualitative dimensions of parental involvement and emotional investment in online social life in decreasing online and offline bullying.